1995
DOI: 10.1177/096120339500400308
|View full text |Cite
|
Sign up to set email alerts
|

Model for the neuromuscular complications of systemic lupus erythematosus

Abstract: The purpose of this study is to evaluate nerve and muscle physiology and histopathology in a murine lupus model. Muscle strength, compound muscle action potentials (distal latency and amplitude), proximal limb muscle, sciatic nerve and joint specimens were studied in MRL/lpr (lupus model) and MRL/++ (control) mice. MRL/lpr mice showed decreased muscle strength (P < 10(-6, Wilcoxon rank sum), lower compound muscle action potential mean amplitude and prolonged distal latency (P = 0.005 and 0.042. Mann-Whitney U-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Both passive and active immunization of normal laboratory mice with either aCL or with ␤2GP1 results in the induction of an experimental antiphospholipid antibody syndrome, including thrombocytopenia, placental infarction and fetal loss, MI, and neurological dysfunction. 38,39 In addition, mice with pinch-clamp injury to vascular endothelium develop a larger clot size with a longer time to dissolution when they are treated with human antiphospholipid antibody compared with control IgG. 40 Taken together, these studies provide important evidence that antiphospholipid antibodies can cause thrombosis and other antibody-mediated clinical manifestations.…”
Section: Discussionmentioning
confidence: 79%
“…Both passive and active immunization of normal laboratory mice with either aCL or with ␤2GP1 results in the induction of an experimental antiphospholipid antibody syndrome, including thrombocytopenia, placental infarction and fetal loss, MI, and neurological dysfunction. 38,39 In addition, mice with pinch-clamp injury to vascular endothelium develop a larger clot size with a longer time to dissolution when they are treated with human antiphospholipid antibody compared with control IgG. 40 Taken together, these studies provide important evidence that antiphospholipid antibodies can cause thrombosis and other antibody-mediated clinical manifestations.…”
Section: Discussionmentioning
confidence: 79%
“…In some of the models it has been shown that there are antibodies to neuronal tissue 22 and these animals are known to have CNS de®cits 23 ± 26 as well as peripheral neuromuscular dysfunction. 27 We have recently presented evidence supporting a speci®c role for aPL in mediating neurological and behavioral changes in animals in which high levels of aPL were induced by immunization with pathogenic monoclonal antibodies. 28 It is therefore relevant to examine the possibility that aPL mediate their effects by direct interaction with neuronal tissue.…”
Section: Introductionmentioning
confidence: 98%
“…9 Motor incoordination, reduced activity, and cognitive impairment have been described in MRL = lpr mice. 10,11 Recently, motor de cits and behavioral hyperactivity were described by our group in a mouse model induced by immunization with pathogenic monoclonal human anticardiolipin antibodies. 12 A model of APS, which is of special interest, is induced by immunization with b 2 -glycoprotein I (b 2 -GPI, also known as apolipoprotein H), which is a major cofactor in the binding of aPL.…”
Section: Introductionmentioning
confidence: 99%